Concept of Lateral Change of Acceleration - Baykal, Orhan (American Society of Civil Engineers (ASCE), 1996)
Due to the very high speeds on railways and motorways, the relationship between the horizontal and vertical geometry of roads with respect to the road dynamics has become very important. In recent publications, new transition curves, used for the design of the horizontal geometry of the road and compared with the old ones on the base of the road dynamics, have been recommended. This paper presents a new equation of lateral change of acceleration, which is examined based on the characteristics of road geometry and vehicle motions. In addition, a few comments are made on some equations for the lateral change of acceleration published by several authors.